2010
DOI: 10.1007/s00432-010-0890-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IGF2 transcript and protein expression by altered methylation in breast cancer

Abstract: Altered methylation of exonic CpG plays an important role in the enhanced transcription/expression of IGF2 in breast tumors. Methylation analysis of exon 9 CpG can be used as a biomarker for upregulation of IGF2 in breast tumor tissue and maybe developed as a diagnostic test in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
3
22
1
Order By: Relevance
“…We found that the expression of several genes were influenced by HMGA1P7 including also genes involved in cancer progression such as Col6a3, Mki67, H19, Igf2, Gpx3 and Leprel1 3031323334353637. Indeed, oncomine analyses and tissue-microarray immunohistochemistry showed overexpression of COL6A3 in colorectal carcinomas that was significantly and directly correlated with Dukes stage, T stage, stage, recurrence and smoking status and then with a poor prognosis30.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We found that the expression of several genes were influenced by HMGA1P7 including also genes involved in cancer progression such as Col6a3, Mki67, H19, Igf2, Gpx3 and Leprel1 3031323334353637. Indeed, oncomine analyses and tissue-microarray immunohistochemistry showed overexpression of COL6A3 in colorectal carcinomas that was significantly and directly correlated with Dukes stage, T stage, stage, recurrence and smoking status and then with a poor prognosis30.…”
Section: Discussionmentioning
confidence: 88%
“…To confirm whether HMGA1P7 works as miRNA sponge for the regulation of H19 and IGF2 expression levels also in human cancer, we evaluated the expression of H19, IGF2 and HMGA1P7 in a panel of breast carcinoma samples by qRT-PCR, since H19 and IGF2 have been reported to be overexpressed in this type of tumor3637. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This may also be occurring at other DMRs, if hypothesized co-regulation with other imprinted regions [37] can be demonstrated. Previous studies have reported an association between circulating IGF2 protein concentrations and high birth weight [46] as well as risk of obesity [47] and several cancers [48, 49] in adulthood, suggesting early exposures may contribute to the variation in birth weight via epigenetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins are usually downregulated in tumors, 64 whereas IGF2 is often overexpressed in many types of cancers and thought to be an oncogene. 70 Finally, our findings suggest the opportunity to identify additional luminal breast tumor markers. Expression of some of the 16 selected genes is usually weak or moderate in breast tissues (Human Protein Atlas).…”
Section: Discussionmentioning
confidence: 74%